Report of the Task Force on Employment Opportunities Overview & Summary of Recommendations - Planning Commission (Planning Commission, 2001)
The 2001 Task Force on Employment Opportunities report, commissioned by India’s Planning Commission, examines the growing unemployment challenge amidst post-reform economic growth. Despite accelerated GDP growth, employment generation remained inadequate, with unemployment rising from 6.03% (1993–94) to 7.32% (1999–2000) and employment growth declining from 2% to under 1%. The report projects an annual labour force increase of 8.3–10 million by 2012, highlighting the need for both quantitative and qualitative job expansion. Recommendations include accelerating GDP growth to 8–9%, sector-specific employment policies, special programs for vulnerable groups, reforms in vocational training and education, and labour market flexibility. Macroeconomic strategies emphasize investment promotion, efficiency enhancement, infrastructure development, and financial system strengthening. Sectoral strategies target agriculture, food processing, small-scale industries, and services. The report underscores an integrated approach linking economic growth with structural employment reforms to generate sustainable, high-quality jobs and address the employment crisis effectively.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Employment Opportunities; Task Force; Economic Reforms; Job Creation; Labour Force; High-Quality Employment; GDP Growth; Sectoral Policies; Skill Development; Small-Scale Industries; Services Sector; Labour Market Reforms